Some results on the simulation of the elastomechanics of ventricle - Sediono, Wahju; Dössel, Olaf (Walter de Gruyter GmbH & Co. KG, 2002)
The imaging of the heart motion plays an important role in the medical science. To support in reaching this goal a simple heart phantom was developed at our research group. This phantom was made of silicon rubber, has a cup form and can beused in the analysis of the dynamics of a beating heart. The hyper elastic properties of the silicon rubber used in the manufacturing of the phantom were determined using Mooney-Rivlin material model. The determination of material parameters was based on a systematic analysis of stress-strain curves reported in the literature. The previously determined material parameters were subsequently implemented in the simulations of the heart’s elastomechanics. A series of simulations with various finite element models of the heart was carried out. The accomplished simulations have also involved a pathological case, where parts of regions within the heart are not contracted.